Fellini satyricon - Fellini, Federico; Petronius Arbiter (Culver City, CA : MGM/UA Home Video, 1988)
Fellini recreates the bawdy and lecherous days of Nero's reign in ancient Rome, a universe unconcerned with human dignity and obsessed with perverse sex.
VHS format.
"M301385"
Italian with English subtitles.
Videocassette release of the 1969 motion picture.
Based on the Satyricon of Petronius Arbiter.
Producer, Alberto Grimaldi ; director, Federico Fellini ; story and screenplay, Federico Fellini and Bernardino Zapponi ; music, Nino Rota.
Keywords: Feature films